INVESTMENT AND RESILIENCE OF THE AGRICULTURAL SECTOR FACING THE COVID 19 CRISIS - Arman Arman; Asep Saefuddin; Fathia Anggriani Pradina; Sri Yusnita Burhan (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2023)
The Covid 19 pandemic appeared suddenly and caused a global crisis that threatens the food security of various countries. The economy was paralyzed, but this did not happen to the agricultural sector in Indonesia. This study aims to (1) examine the role of the agricultural sector during the Covid-19 pandemic crisis, (2) analyze the level of investment efficiency in the growth of the agricultural sector before and during the Covid 19 pandemic crisis, and (3) formulate a policy solution for the agricultural sector facing the crisis. The research method uses Incremental Capital Output Ratio (ICOR) and descriptive methods. We are of the view that the agricultural sector has the resilience to face the Covid 19 crisis marked by positive growth, the second largest employment absorption, increased farmer exchange rates and exports. The performance of the agricultural sector was still efficient in the 2012-2019 range even though the ICOR value relatively rose and growth tended to decline. The agricultural sector faces food supply chain constraints, food loss and loss of added value. The triggers are long distribution chains, technology, high input costs, road and transportation infrastructure. The government and industry must support the provision of supporting infrastructure, namely technology, infrastructure, human resources and institutional strengthening. Diversification of food, industry 4.0, high-quality seeds and food supply chain as part of mitigation and adaptation needs to be supported by technology, human resources and strong institutions. The agricultural sector has proven to play a vital role in economic resilience.